Swyer–James–McLeod's syndrome and pneumothorax on same side: delay in chest drain removal despite full expansion. (23rd February 2011) - Anwar, Nadeem; Yadavilli, Rajesh; Ibrahim, Kamal
Abstract : Swyer–James–McLeod's syndrome (SJMS) occurs as a result of childhood recurrent respiratory infections. As this condition presents with few symptoms, if any, it may pass unnoticed until adulthood. The authors are presenting a case of a 17-year-old male admitted with spontaneous pneumothorax. Even though his lung expanded, his chest x-rays still mimicked a pneumothorax. Chest CT pulmonary angiogram was needed to confirm the diagnosis of unilateral SJMS. Diagnostic difficulty arose because both conditions were on the same side.